ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI JAGUNG (Zea mays L) DI KECAMATAN DARUL HASANAH KABUPATEN ACEH TENGGARA - Mamang Sari; Rini Mastuti; Kiagus M. Zain Basriwijaya (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to analyze the factors that affect the income of corn farming (Zea mays L) in Darul Hasanah District, Southeast Aceh Tenggara. The method of determining the sample using a sampling technique, namely probability sampling as many as 62 respondents consisting of 8 villages with a simple random sampling method. The data collected in this study are primary data and secondary data. Data processing was carried out using SPSS 22 computer software. The data analysis method used was the classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), multiple linear regression analysis and hypothesis testing (partial test/t test, simultaneous test/test F and test adjusted R Square2). The results of this study indicate that the variables of experience (X1), knowledge (X2), attitude (X3), skills (X4) and land area (X5) have a significant effect on maize farming income (Zea mays L) in Darul Hasanah District, Southeast Aceh Tenggara.